Implementation of the Beveridge Report (letter) - Evans, T. G.
1943-03-15 1943 1940s 1 page TONYREFAIL & DISTRICT UNEMPLOYED SOCIAL SERVICE COMMITTEE PRESIDENT: LIEUT. COL. SIR RHYS WILLIAMS, BART., K.C., D.S.O. VICE-PRESIDENT; REV. G. ISAAC, B.D., VICAR OF TONYREFAIL. PATRONS: COUNCILLOR TOM YOUNG. MR. E. LLOYD EDWARDS. MR. D. COLBY JONES. CHAIRMAN: MR. WALTER HUSSEY. VICE-CHAIRMAN: MR. DD. HY. JOHN. HON. TREASURER: MR. S. HERAPATH. HON. SECRETARY: [MR. R.E. REES] T.G. Evans Unemployed Social Club, Tonyrefail, Glam. Mar 15 1943 Sir Walter Citrine Secretary TUC Sir I have been instructed by the Committee of the above club, in conjunction with the Committee of the Tonyrefail & District Old Age Pensioners, representing approximately 500 members, to ask you to do your utmost to implement the Beveridge Report in its entirety. My Committee wishes to emphasise the fact that the Report has been broadcast to the whole world, and approved wholeheartedly in the Colonies and Allied Countries. Why has it been shelved? Is it to meet the same fate as promises made during the previous World War. Homes fit for Heroes Etc.? The members are generally asking "What is the meaning of the Political Acrobatics? Fulsome and World Wide praise and commendation one moment and what amounts to a rejection the next" I am to state definitely that we expect our Member of Parliament to oppose the shelving of the Report with all the power at his command, as the constituents in this Division have made up their minds that the Country spending some 14 millions a day for Destructive War can surely afford a fraction of that amount for constructive purposes. Yours sincerely, T.G. Evans Hon Sec 292/150.5/5/86